Тензорная модель гарантированного обеспечения нормированных показателей качества обслуживания в ткс - Евсеева, О. Ю. (УНДІЗ, 2008)
A temporary tensor model of TCS represented as orthogonal one- product bipolar network in Riemannian space is proposed. Characteristic feature of this model as against of those obtained before is the introduction of co-ordinates of basic circuit and basic intercections. In the context of this model the requirements for QoS were determined in terms of end-to-end data transmission delays and subnets transmission delays between a pair of sender-reciever taking into account the nature of flow traffic.
Keywords: ТЕНЗОРНАЯ МОДЕЛЬ; QoE; КАЧЕСТВО ОБСЛУЖИВАНИЯ; ТКС